1989
DOI: 10.1177/107906328900200202
|View full text |Cite
|
Sign up to set email alerts
|

The Measurment of the Cognitive Distortions of Child Molesters

Abstract: The measurement of the cognitive distortions of child molesters. Annals of Sex 2, 135-153. Two hundred and forty child molester paraphiliacs, 48 non-child molesting paraphiliacs and 86 non-paraphiliacs were administered a 29 item Likert scale of statements designed to determine: 1) if cognitive distortions concerning child molestation exist among child molesters and (2) if child molesters can be discriminated from non-child molesters by assessing their cognitive distortions. Factor analysis yielded six factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 4 publications
(4 reference statements)
0
38
0
4
Order By: Relevance
“…Such favourable discriminations have been found for other measures, including Abel et al's (1989) Abel and Becker Cognitions Scale (Hayashino, Wurtele, & Klebe, 1995;Stermac & Segal, 1989), and the Hanson Sex Attitudes Questionnaire (Hanson, Gizzarelli, & Scott, 1994). Other studies, however, have raised doubts about the discriminative ability of cognitive distortion measures (Abel et al, 1989;Fisher, Beech, & Browne, 1999;Tierney & McCabe, 2001). For example, Abel et al (1989) were unable to discriminate CMs from non-CM paraphilics on the Abel and Becker Cognitions Scale.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Such favourable discriminations have been found for other measures, including Abel et al's (1989) Abel and Becker Cognitions Scale (Hayashino, Wurtele, & Klebe, 1995;Stermac & Segal, 1989), and the Hanson Sex Attitudes Questionnaire (Hanson, Gizzarelli, & Scott, 1994). Other studies, however, have raised doubts about the discriminative ability of cognitive distortion measures (Abel et al, 1989;Fisher, Beech, & Browne, 1999;Tierney & McCabe, 2001). For example, Abel et al (1989) were unable to discriminate CMs from non-CM paraphilics on the Abel and Becker Cognitions Scale.…”
mentioning
confidence: 96%
“…Other studies, however, have raised doubts about the discriminative ability of cognitive distortion measures (Abel et al, 1989;Fisher, Beech, & Browne, 1999;Tierney & McCabe, 2001). For example, Abel et al (1989) were unable to discriminate CMs from non-CM paraphilics on the Abel and Becker Cognitions Scale.…”
mentioning
confidence: 96%
“…Others have either found no significant differences (e.g., Tierney & McCabe, 2001), or reported cognitive distortion scores so low for child molesters that it would seem pointless employing a control group for comparison (Kolton, Boer, & Boer, 2001;Langevin, 1991). For example, Langevin (1991) found that, on average, 75% of child molesters undergoing a pretrial assessment picked the least distorted option (i.e., "strongly disagree") on the Abel and Becker Cognition Scale (Abel et al, 1989).…”
Section: Do Child Molesters Deliberately Fake Good On Cognitive Distomentioning
confidence: 96%
“…Factor analysis has indicated that the scale is one-dimensional (Abel et al, 1989;Hanson, Gizzarelli, & Scott, 1994). Scores range from 1 to 5, where lower scores are indicative of a greater degree of acceptance towards adult sexual contact with children.…”
Section: Cognition Scalementioning
confidence: 98%
“…Reliability is good, with an alpha coefficient of .92 for internal consistency (Hanson et al, 1994). A Pearson product-moment coefficient of .76 indicated good test-retest reliability (Abel et al, 1989).…”
Section: Cognition Scalementioning
confidence: 99%